Determinants of the Profitability of Catfish Production Among Farmers in Oyo State, Nigeria. - Adeosun, O.M.; Olaoye, O.J.; Ojebiyi, W.G.; Adeosun, F.I.; Soyoye, V.O.; Ajiboye, E.O.; Onaolapo, M.R. (Nigerian Journal of Animal Science, 2026)
This study examined the profitability of catfish production in Oyo State, Nigeria. A total of 120 african catfish (Clarias gariepinus) producers were randomly sampled and data were collected through an interview guide (questionnaire). Descriptive and inferential statistics. (Frequencies, Percentages, means, and Standard deviation, Budgetary analysis, and multiple regression analytical techniques) were employed for data analysis. Findings showed that majority of the catfish farmers were male (99.2%), and are into full time catfish farming (82.5%), this group have less than 20years experience in catfish farming with mean fish farming experience of 12.1±5.9 years. More than half (57.5%) had tertiary education while 41.7% had either primary or secondary education. The total cost of catfish production was estimated to be ₦2,451,881.0 per production cycle, and the total revenue generated was ₦2,752,883.3 per production cycle. The net farm income was ₦301,002.4 per production cycle. High cost of feeds (x̄ = 3.32±0.75), high cost of pond construction (x̄ = 3.05±1.17), inadequate fund (x̄ = 2.92±0.73) and high cost of fish seeds (x̄ = 2.29±1.16) were severe constraints to catfish farming. The regression analysis showed that the quantity of catfish harvested (β = 0.636, p≤0.01), price per kilogram of table size fish (β = 0.246, p≤0.05) and kind of fish seed stocked (β = 0.204, p≤0.05) were significant determinants of profitability of catfish production. The study concluded that catfish production was a profitable enterprise, and improving infrastructural facilities can enhance productivity and profitability.